2018
DOI: 10.1016/j.celrep.2018.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Differentially Regulates Insulin Production and Insulin Sensitivity

Abstract: SUMMARY Autophagy, a stress-induced lysosomal degradative pathway, has been assumed to exert similar metabolic effects in different organs. Here, we establish a model where autophagy plays different roles in insulin-producing β cells versus insulin-responsive cells, utilizing knockin (Becn1F121A) mice manifesting constitutively active autophagy. With a high-fat-diet challenge, the autophagy-hyperactive mice unexpectedly show impaired glucose tolerance, but improved insulin sensitivity, compared to mice with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 41 publications
8
105
0
1
Order By: Relevance
“…In fact, it has been shown that genetic hyperactivation of autophagy exacerbates glucose intolerance in mice fed a high fat diet; however, this change can be reversed by transient inhibition of autophagy. Therefore, autophagy is considered a double-edged sword that can promote either cell survival or death [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that genetic hyperactivation of autophagy exacerbates glucose intolerance in mice fed a high fat diet; however, this change can be reversed by transient inhibition of autophagy. Therefore, autophagy is considered a double-edged sword that can promote either cell survival or death [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sharma et al (Sharma et al, ) recently reported the autophagy promoting effect of clerodane furano diterpene glycoside from T. cordifolia . Autophagy regulates body weight via differentially regulating insulin production and insulin sensitivity (Yamamoto et al, ). TCSE may contain furano diterpene glycosides, which could regulate insulin secretion in pancreatic beta cells and insulin sensitivity in adipocytes via modulating autophagy machinery.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate Becn1 functions in vivo, a knock-in mouse model carrying a Becn1 mutation (Becn1 F121A ) resulting in constitutively active autophagy has been recently generated (Rocchi et al, 2017). In these mice Phe121 is mutated into alanine resulting in disruption of the BECN1-BCL2 binding and constitutive activation of BECN1 and autophagy in multiple tissues, including liver (Fernandez et al, 2018;Rocchi et al, 2017;Yamamoto et al, 2018).…”
Section: Constitutional Hyperactivation Of Beclin-1 Enhances Ammonia mentioning
confidence: 99%